Sports injuries (Oxford University Press, 2011)
Description: The current high profile in the UK of sports and exercise medicine has been reflected in recent years by its acceptance as a stand-alone specialty and the development of the faculty of sports and exercise medicine. Written by a truly multinational list of contributors who work within, and represent the cutting edge of the discipline, Sports Injuries is in full colour throughout and contains hundreds of illustrations to aid diagnosis and understanding. It is organised by anatomical region and by sport, and also covers basic sciences such as functional anatomy, tissue injury and repair, and principles of examination and treatment to further enhance understanding.